SURFACE-ANALYSIS OF LANTHANUM-MODIFIED COBALT CATALYSTS - INVITED LECTURE - LEDFORD, JS; KIM, YM; HOUALLA, M; PROCTOR, A; HERCULES, DM (ROYAL SOC CHEMISTRY, 1992)
The effect of the addition of La on the structure of 3% m/m Co/Al2O3 catalysts has been studied by the combined use of X-ray photoelectron spectroscopy, Raman spectroscopy, X-ray diffraction and gravimetric analysis. It was shown that La exists as a highly dispersed La-Al2O3 interaction species for alumina carriers impregnated with La and calcined at 600-degrees-C. For 3% m/m Co/Al2O3 catalysts containing La, little effect is observed for La/Al atomic ratios below 0.0075. For higher La loadings, an increase in Co dispersion is observed owing to suppression of Co3O4 formation. Tetrahedral Co2+ and a small amount of an La-Co surface phase are formed. Formation of tetrahedral Co2+ is caused by migration of Co from the La-Co surface phase into the alumina support during calcination at 600-degrees-C.
Keywords: PHOTOELECTRON-SPECTROSCOPY